EXPLORING THE USE OF NARRATIVE TEXT IN TEACHING READING COMPREHENSION IN EFL CLASSROOM - Rohmana, Wahyu Indah Mala; Amalia, Kharisma Rizki (Proceeding of International Conference on Islamic Education (ICIED); Vol 7 No 1 (2022): Proceeding of International Conference on Islamic Education (ICIED), 2022)
This study investigated the use of narrative text in teaching reading comprehension. It aims to find out the implementation of teaching reading comprehension through narrative text and the teacher's preception toward reading comprehension through narrative text. This study is descriptive qualitative method using observation and interview to collect the data since the intended results is the brief description of teaching reading comprehension. The finding of the study shows how the teacher implemented narrative text in teaching reading comprehension. It also shows the students’ understanding during the explanation of the content of narrative text. The students got a lot of vocabularies and new knowledge including the moral message implied in narrative text. Teaching reading comprehension through narrative text can boost the motivation of students and the students are more active in the class.